Making of Compost Fertilizer through Waste Raw Materials for Water Spinach Plants in Polybag - Hasriati Nasution; Asmadi Saat; Yusfaneti Yusfaneti (Bulletin of Community Engagement, 2023)
The article aimed giving an assistance of making compost fertilizer through waste raw materials for water spinach Plants in Polybag. The researchers used Community Based Research (CBR). This service was in the form of material counseling and direct demonstrations in the field for three months starting from a preliminary survey, determining the schedule until conducting outreach counseling in composting from waste sources. The Extension was carried out in two stages, namely by providing materials related composting and followed by carried out a direct demonstration in the field on how to make compost it with children at Yayasan Kesejahteraan Anak (YKA) Jambi City. The article conducted at Yayasan Kesejahteraan Anak (YKA), with 50 students as participants. The results showed that this assistance giving significant results of children because they have skilled in making compost from waste and planting water spinach in polybags where the results gave nutrition of Yayasan Kesejahteraan Anak (YKA). Keywords: Making Compost Fertilizer, Compost Fertilizer, Assistance Students